2021
DOI: 10.3390/s21165395
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Algorithms on Low-Power and High-Performance Devices for Edge Computing Environments

Abstract: The synergy between Artificial Intelligence and the Edge Computing paradigm promises to transfer decision-making processes to the periphery of sensor networks without the involvement of central data servers. For this reason, we recently witnessed an impetuous development of devices that integrate sensors and computing resources in a single board to process data directly on the collection place. Due to the particular context where they are used, the main feature of these boards is the reduced energy consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…These papers had more features available for consideration through the k-means algorithm, which led to an increase in the efficiency of using that algorithm in solving a specific problem. Other related research includes parallel clustering on low-power devices in edge computing environments [ 30 ] or methods for delivering sensor data and storing them in an IoT environment [ 31 , 32 ].…”
Section: Related Workmentioning
confidence: 99%
“…These papers had more features available for consideration through the k-means algorithm, which led to an increase in the efficiency of using that algorithm in solving a specific problem. Other related research includes parallel clustering on low-power devices in edge computing environments [ 30 ] or methods for delivering sensor data and storing them in an IoT environment [ 31 , 32 ].…”
Section: Related Workmentioning
confidence: 99%
“…In the future, benchmarking and extending the solution towards other types of GPUs will be of interest, specifically mobile and embedded type of compute devices in multi-node systems. It has been demonstrated that such devices offer less power demanding computing 40,41 and exploration of performance-power trade-offs using power capping might result in non-trivial configurations under more strict power limitations as compared to powerful GPUs in the traditional servers and HPC systems. Additionally, extending the implementation to use available CPU cores for computations will be performed, according to the concept presented in Appendix E.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Power consumption during ML forecasts on edge is a critical issue due the limited power availability for IoT nodes. Therefore, power consumption optimization on the edge using ML is investigated in [27][28][29]. Also, in [30] ML is applied on time-series data from IoT sensors in order to predict failure in a slitting machine.…”
Section: Platforms Used On the Edgementioning
confidence: 99%